Deciphering the high‐quality genome sequence of coriander that causes controversial feelings. Issue 6 (5th February 2020) - Song, Xiaoming; Wang, Jinpeng; Li, Nan; Yu, Jigao; Meng, Fanbo; Wei, Chendan; Liu, Chao; Chen, Wei; Nie, Fulei; Zhang, Zhikang; Gong, Ke; Li, Xinyu; et al.
Summary: Coriander ( Coriandrum sativum L. 2 n  = 2 x  = 22), a plant from the Apiaceae family, also called cilantro or Chinese parsley, is a globally important crop used as vegetable, spice, fragrance and traditional medicine. Here, we report a high‐quality assembly and analysis of its genome sequence, anchored to 11 chromosomes, with total length of 2118.68 Mb and N50 scaffold length of 160.99 Mb. We found that two whole‐genome duplication events, respectively, dated to ~45–52 and ~54–61 million years ago, were shared by the Apiaceae family after their split from lettuce. Unbalanced gene loss and expression are observed between duplicated copies produced by these two events. Gene retention, expression, metabolomics and comparative genomic analyses of terpene synthase (TPS) gene family, involved in terpenoid biosynthesis pathway contributing to coriander's special flavour, revealed that tandem duplication contributed to coriander TPS gene family expansion, especially compared to their carrot counterparts. Notably, a TPS gene highly expressed in all 4 tissues and 3 development stages studied is likely a major‐effect gene encoding linalool synthase and myrcene synthase. The present genome sequencing, transcriptome, metabolome and comparative genomic efforts provide valuable insights into the genome evolution and spice trait biology of Apiaceae and other related plants, and facilitated further research into important gene functions and crop improvement.